2022
DOI: 10.3390/ijms232315317
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ceramides and Lysosomes in Extracellular Vesicle Biogenesis, Cargo Sorting and Release

Abstract: Cells have the ability to communicate with their immediate and distant neighbors through the release of extracellular vesicles (EVs). EVs facilitate intercellular signaling through the packaging of specific cargo in all type of cells, and perturbations of EV biogenesis, sorting, release and uptake is the basis of a number of disorders. In this review, we summarize recent advances of the complex roles of the sphingolipid ceramide and lysosomes in the journey of EV biogenesis to uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 202 publications
1
22
0
Order By: Relevance
“…As per our estimation, the membrane of approximately 60 EVs equates to the ciliary membrane (Figure S3A). Ceramide is a pivotal membrane lipid essential for EV formation 2,18 . Ceramide is also an important lipid for cilia formation, ciliary length and ciliary signaling 19 .…”
Section: Resultsmentioning
confidence: 99%
“…As per our estimation, the membrane of approximately 60 EVs equates to the ciliary membrane (Figure S3A). Ceramide is a pivotal membrane lipid essential for EV formation 2,18 . Ceramide is also an important lipid for cilia formation, ciliary length and ciliary signaling 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have also shown that phosphoinositides, ceramides, and the lipid composition of the endosomal membrane as a whole are key factors in the biogenesis of ILVs [ 38 , 39 ]. It is also worth mentioning that ESCRT-independent mechanisms have been delineated as alternative systems for the formation of ILVs, and that vesicle release by cells could also occur from lysosomes [ 40 , 41 , 42 ]. In addition, a process involving tetraspanin enrichment appears to be important for membrane remodeling and ILVs formation [ 43 , 44 ].…”
Section: Exosomes Are Small Specialized Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…20 Several research groups have investigated the feasibility of using EV to transport pharmaceuticals, nucleic acids, and proteins for therapeutic purposes. 21,22 In this study, we identified potential candidate genes using an in vivo genetic loss-of-function screening approach based on CRISPR-Cas9 genome editing to identify genes that increase the sensitivity or cause radioresistance in an orthotopic GBM model. Ferroptosis, triggered by the enzyme glutathione synthetase (GSS), has been shown to be a determinant in radiosensitization.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, EV proteins include CD47, a transmembrane protein linked with integrins that helps shield cells from phagocytosis . Several research groups have investigated the feasibility of using EV to transport pharmaceuticals, nucleic acids, and proteins for therapeutic purposes. , …”
Section: Introductionmentioning
confidence: 99%